ENHANCING GROWTH AND SURVIVAL OF WHITE TURMERIC (Kaempferia rotunda Linn.) PLANLETS THROUGH DIVERSE ACCLIMATIZATION MEDIA - Murgayanti, Murgayanti; Hapsary, Almira Abiira; Suminar, Erni; Aprilia, Eva (Jurnal Agrotek Tropika, 2025)
White turmeric (Kaempferia rotunda L.) holds significant potential due to its numerous health benefits, resulting in increasing demand. Tissue culture techniques are used to rapidly produce high-quality seedlings. This study aims to determine the optimal growth medium combination for the acclimatization phase of white turmeric plantlets.The research utilized a Randomized Block Design (RBD) with various growth medium combinations as treatments. A total of seven combinations were used, integrating soil, rice husk charcoal, cocopeat, vermiculite, and sand in equal proportions. The combinations included Soil; Soil + Rice Husk Charcoal; Soil + Cocopeat; Soil + Vermiculite; Soil + Sand; Soil + Cocopeat + Charcoal; Soil + Cocopeat + Vermiculite; Soil + Cocopeat + Sand; Soil + Vermiculite + Charcoal; and Soil + Sand + Charcoal. The results indicate that acclimatization medium combinations significantly influence plantlet growth. The Soil + Rice Husk Charcoal (1:1) medium achieved the best overall growth, with an average plant height of 17.67 cm, 2.11 leaves, a root length of 21.36 cm, and a root volume of 5.5 ml. Furthermore, the Soil + Cocopeat + Rice Husk Charcoal (1:1:1) medium produced the highest root fresh weight, at 5.31 grams. These findings highlight the importance of optimizing growth medium combinations to enhance the growth and quality of white turmeric plantlets during acclimatization.